2017
DOI: 10.1177/0030222817719805
|View full text |Cite
|
Sign up to set email alerts
|

The Associations of Complicated Grief, Depression, Posttraumatic Growth, and Hope Among Bereaved Youth

Abstract: Research on the association between complicated grief (CG), hope, and posttraumatic growth (PTG) among bereaved youth is limited. Measures of CG, depression, hope, and PTG were completed by 85 youth (aged 7-18 years). Results indicated a strong positive relationship between CG and depressive symptoms, an inverse relationship between hope and depressive symptoms, and a moderate positive relationship between hope and PTG. There was no significant association between CG and hope or between CG and PTG. Higher leve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
22
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 46 publications
3
22
1
Order By: Relevance
“…Complicated grief is common in adolescent suicide survivors who have experienced bereavement due to suicide in an intimate relationship, and it is reported to be closely associated with psychiatric symptoms such as depression [30], anxiety, PTSD, and suicide ideation [31]. Some studies have suggested that there may be a long time-gap between the time of bereavement and the expression of psychiatric symptoms such as depression and anxiety [31], and there is a need to prioritize treatment of complicated grief [32]. This is derived from the fact that complicated grief is accompanied by difficulty accepting bereavement, anger about bereavement, and loss of meaning in life after bereavement, and can persist throughout a lifetime, existing as a clearly separate but related construct with other psychiatric symptoms such as depression, anxiety, and PTSD [32,33].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Complicated grief is common in adolescent suicide survivors who have experienced bereavement due to suicide in an intimate relationship, and it is reported to be closely associated with psychiatric symptoms such as depression [30], anxiety, PTSD, and suicide ideation [31]. Some studies have suggested that there may be a long time-gap between the time of bereavement and the expression of psychiatric symptoms such as depression and anxiety [31], and there is a need to prioritize treatment of complicated grief [32]. This is derived from the fact that complicated grief is accompanied by difficulty accepting bereavement, anger about bereavement, and loss of meaning in life after bereavement, and can persist throughout a lifetime, existing as a clearly separate but related construct with other psychiatric symptoms such as depression, anxiety, and PTSD [32,33].…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have suggested that there may be a long time-gap between the time of bereavement and the expression of psychiatric symptoms such as depression and anxiety [31], and there is a need to prioritize treatment of complicated grief [32]. This is derived from the fact that complicated grief is accompanied by difficulty accepting bereavement, anger about bereavement, and loss of meaning in life after bereavement, and can persist throughout a lifetime, existing as a clearly separate but related construct with other psychiatric symptoms such as depression, anxiety, and PTSD [32,33]. One previous study [34] has demonstrated that the core resources to alleviate the symptoms of grief in adolescents are hope and positive expectations about the future.…”
Section: Discussionmentioning
confidence: 99%
“…Time since the loss seems to be an important factor associated with PTG ( Waugh et al, 2018 ). A study on bereaved youth also did not find this curve relationship ( Salloum et al, 2019 ). These results suggested that the patterns of the relationship between grief and growth may vary in different samples.…”
Section: Discussionmentioning
confidence: 99%
“…Lots of studies have examined the relationship between grief and PTG but with conflicting results. Some studies show a negative correlation ( Engelkemeyer and Marwit, 2008 ), some positive ( Xu et al, 2015 ), or no significant correlation at all ( Salloum et al, 2019 ). These inconsistent findings suggest that the relationship between grief and PTG may vary in different bereaved samples.…”
Section: Introductionmentioning
confidence: 99%
“…Other adverse effects include rumination, feelings of guilt for not having prevented the death, and guilt for positive emotions after a loss (Shear, 2008). Combined with a decrease in hope, complicated grief predicts greater depressive and somatic symptoms (Herberman Mash et al, 2013;Salloum et al, 2019). Research suggests that between 10-21% of bereaved students eventually develop complicated grief (Cox et al, 2015;Herberman Mash et al, 2013;Schnider et al, 2007).…”
Section: Impact Of Unresolved Griefmentioning
confidence: 99%